1985
DOI: 10.1172/jci111859
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of procollagen gene expression by retinoids. Inhibition of collagen production by retinoic acid accompanied by reduced type I procollagen messenger ribonucleic acid levels in human skin fibroblast cultures.

Abstract: Recent clinical observations have suggested that retinoids, which are in frequent use in dermatology, can affect the connective tissue metabolism in skin and other tissues. In this study, we examined the effects of several retinoids on the metabolism of collagen by human skin fibroblasts in culture. Incubation of cultured fibroblasts with all-trans-retinoic acid or 13-cis-retinoic acid, in 10-5 M or higher concentrations, markedly reduced the procollagen production, as measured by synthesis of radioactive hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…The marked difference in the potency of retinol versus retinoic acid has been previously noted and parallels the observed differences in their serum concentrations (retinol 10-6 M versus retinoic acid < 10-9 M) as well as the intracellular Ito cell concentrations of the respective cytosolic binding proteins (22,24,42). The medically used and related 13-cis-retinoic acid caused similar inhibition of cell proliferation at the 10-6-lo-8 M range.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…The marked difference in the potency of retinol versus retinoic acid has been previously noted and parallels the observed differences in their serum concentrations (retinol 10-6 M versus retinoic acid < 10-9 M) as well as the intracellular Ito cell concentrations of the respective cytosolic binding proteins (22,24,42). The medically used and related 13-cis-retinoic acid caused similar inhibition of cell proliferation at the 10-6-lo-8 M range.…”
Section: Methodssupporting
confidence: 72%
“…lOOX lower molar concentrations than used in previous studies with retinol ( 19,20). This difference in sensitivity to retinol versus retinoic acid has been previously noted in other cell systems and may be especially important in any potential applications in vivo (24,42). In other cell systems, however, the response to retinoic acid may differ considerably.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We felt it was relevant, therefore, to compare levels of expression of these two genes by fibroblasts in culture in the presence of TGF-␤1 or indomethacin, which increase procollagen-I transcripts (25,26), and in the presence of phorbol ester or retinoic acid, which inhibit procollagen-I gene expression (27,28). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the therapeutic effect of etretinate in LS could be at least partly due to its effect on the epidermis. The adaptation of epidermal cells to etretinate and the subsequent modu lation of their differentiation lead to the restoration of normal structure and func tion [7], Previous studies have shown that etretinate has also anti-inflammatory properties and that it can stimulate collagen production [7,21]. In patients receiving etretinate, we observed a decrease in the number of inflammatory cells but an in crease in the number of invading fibroblasts.…”
Section: Discussionmentioning
confidence: 55%